Fluorine substituted methoxyphenylalkyl amides as potent melatonin receptor agonists. Issue 3 (6th March 2019) - Tsotinis, Andrew; Kompogennitaki, Rodanthi; Papanastasiou, Ioannis; Garratt, Peter J.; Bocianowska, Alina; Sugden, David
Abstract : A series of fluorine substituted methoxyphenylalkyl amides were prepared with different orientations of the fluorine and methoxy groups with respect to the alkylamide side chain and with alkyl sides of differing lengths ( n = 1–3). Abstract : A series of fluorine substituted methoxyphenylalkyl amides were prepared with different orientations of the fluorine and methoxy groups with respect to the alkylamide side chain and with alkyl sides of differing lengths ( n = 1–3). β-Dimethyl and α-methyl derivatives were also synthesised. The compounds were tested as melatonin agonists and antagonists using the pigment aggregation of Xenopus melanophores as the biological assay. A number of these compounds were potent melatonin agonists, the potency depending on the length of the alkyl chain, the orientation of the methoxy and fluorine substituents, the amide chain length and, for the ethyl side-chain analogues, the presence of β-substituents.